Legal Analysis of Foreign Investment Limited Liability Companies Establishing Business Entities - Louis Hananta Kusuma; Nynda Fatmawati Octarina (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Globalization and economic liberalization have increased foreign investment in Indonesia, including through the establishment of Foreign Investment Limited Liability Companies (PT PMA). PT PMA often establishes other business entities, such as Limited Partnership (CV), to maximize its business. This phenomenon raises legal questions regarding the legitimacy, regulations, and implications of establishing a business entity by PT PMA. This research aims to find the legal ratio of foreign investment legal entities in the form of limited liability companies and to analyze the status of limited partnerships established by limited liability companies that have the status of foreign capital limited liability companies. The type of research used in this research is normative legal research. The problem approaches used in compiling this research are the conceptual approach, the statutory approach, and the comparative approach. The results of the research found that Limited Liability Companies can establish limited partnerships, by becoming passive partners, and Limited Liability Companies with foreign capital can establish limited partnerships, this is because there is no prohibition.